Audiovisual Temporal Processing in Children and Adolescents With Schizophrenia and Children and Adolescents With Autism: Evidence From Simultaneity-Judgment Tasks and Eye-Tracking Data. (May 2022) - Zhou, Han-yu; Cui, Xi-long; Yang, Bin-rang; Shi, Li-juan; Luo, Xue-rong; Cheung, Eric F. C.; Lui, Simon S. Y.; Chan, Raymond C. K.
Impaired audiovisual temporal integration, manifested as an abnormally widened temporal-binding window (TBW) for integrating sensory information, is found in both autism spectrum disorder (ASD) and schizophrenia (SCZ) and contributes to aberrant perceptual experiences and impaired social communication. We conducted two experiments using age-comparable samples of participants with early-onset SCZ and participants with ASD. Sophisticated paradigms, including a unisensory temporal-order-judgment task (TOJ), an audiovisual-simultaneity-judgment task (SJ), and an eye-tracking task were used. Results showed generalized deficits in temporal processing in SCZ ranging from unisensory to multisensory modalities and from nonspeech to speech stimuli. In contrast, the widened TBW in ASD mainly affected speech stimuli processing. Applying the eye-tracking task with ecologically valid linguistic stimuli, we found that both participants with SCZ and participants with ASD exhibited reduced sensitivity of detecting audiovisual speech asynchrony. This impaired audiovisual speech integration correlated with negative symptoms. Although both ASD and SCZ have impaired multisensory temporal integration, ASD impairs speech-related processing, and SCZ is associated with generalized deficits.